ANALISIS PENGELOLAAN KEUANGAN PADA TOKO KUE JHINNY CAKE SALOPA KABUPATEN TASIKMALAYA - Salsa Rofiatul Ula; Nurnawati, Rani (LPPM IAIT, 2024)
Financial management is very important for individuals and companies, because it can manage all forms of financial activities well. Small, Micro and Medium Enterprises at the Jhinny Cake Cake Shop are a case study in this research topic regarding financial management analysis. Jhinny Cake Cake Shop operates in the food sector. As his business continues to grow, problems also occur internally in his business, especially poor financial management. The purpose of this research is to determine the financial management implemented at the Jhinny Cake Salopa Cake Shop, Tasikmalaya Regency. This research study uses qualitative research methods. The data source in this research is primary data through interviews with owners, employees and consumers at the Jhinny Cake Salopa Cake Shop, Tasikmalaya Regency, then secondary data is obtained through books, journals, articles from the internet, and collecting data and documents in the shop. Jhinny Cake Salopa Cake, Tasikmalaya Regency which is related to the research discussion. The data collection techniques used are through observation, interviews and documentation. The research results show that the financial management carried out at the Jhinny Cake Cake Shop is still not optimal in terms of financial management, the shop owner still uses manual recording and does not use financial accounting rules.